2018
DOI: 10.1017/s1470542717000125
|View full text |Cite
|
Sign up to set email alerts
|

The Intonation of Polar Questions in North American (“Heritage”) Icelandic

Abstract: Using map task data, this paper investigates the intonation of polar questions in North American (heritage) Icelandic, and compares it to the intonation of polar questions in Icelandic as spoken in Iceland and in North American English as spoken in Manitoba, Canada. The results show that intonational features typical of Icelandic polar questions are present to a considerable extent in heritage Icelandic. Furthermore, intonational features typical of North American English polar questions can frequently be obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Similarly, the default rise-fall intonation of Icelandic were found in both heritage Icelandic and North American English. However, when comparing the frequency of these contours across groups, Dehé (2018) found that heritage Icelandic demonstrated significantly more low rises (56.7%) than Icelandic of Iceland (10.5%) and significantly fewer low rises than North American English (78.9%). Regarding the rise-fall contours typical of Icelandic, the opposite pattern was found; heritage Icelandic showed significantly fewer rise-falls (32.5%) than Icelandic of Iceland (65%) and significantly more rise-falls than North American English (6.3%).…”
Section: Variability In the Intonation Of Heritage Languages And Monolingual Varietiesmentioning
confidence: 95%
See 2 more Smart Citations
“…Similarly, the default rise-fall intonation of Icelandic were found in both heritage Icelandic and North American English. However, when comparing the frequency of these contours across groups, Dehé (2018) found that heritage Icelandic demonstrated significantly more low rises (56.7%) than Icelandic of Iceland (10.5%) and significantly fewer low rises than North American English (78.9%). Regarding the rise-fall contours typical of Icelandic, the opposite pattern was found; heritage Icelandic showed significantly fewer rise-falls (32.5%) than Icelandic of Iceland (65%) and significantly more rise-falls than North American English (6.3%).…”
Section: Variability In the Intonation Of Heritage Languages And Monolingual Varietiesmentioning
confidence: 95%
“…Although research on heritage language intonation is scarce, studies have shown that heritage speakers are different from monolingual speakers in the distribution of pitch accents and boundary tones (Dehé 2018;Queen 2001;Rao 2016;Robles-Puente 2014), in the phonetic implementation of pitch accents (Colantoni et al 2016;Zuban et al 2020), or in the use of prosody to express pragmatic functions (Bullock 2009;Hoot 2017;Kim 2019). Some possible explanations for heritage speakers' divergent intonation patterns are the emergence of new tonal categories due to hybridization of heritage and majority language categories (Queen 2001;Rao 2016), the mix of intonation patterns or prosodic strategies found in both heritage and majority languages (Bullock 2009;Kim 2019;Robles-Puente 2014), or the use of fine-grained acoustic cues similar to or approaching those in the majority language (Colantoni et al 2016;Zuban et al 2020).…”
Section: Variability In the Intonation Of Heritage Languages And Monolingual Varietiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Icelandic question intonation has not yet been the focus of much experimental research. The default intonational contour of both polar questions and wh-questions is falling to a low boundary tone (L%) [13], [14], [15], [16]. According to [15, p. 323], questions with rising intonation (H%) "have special connotations" such as, for example, impatience or surprise.…”
Section: Icelandic Question Intonationmentioning
confidence: 99%
“…For the phonological analysis, prenuclear and nuclear pitch accents, as well as boundary tones were annotated following previous intonational analyses of Icelandic in the autosegmental-metrical framework (e.g. [24], [16]; second tier from top in Figure 1). Along with H% and L%, boundaries were labelled M% (N=19), if contours ended in a mid-level.…”
Section: Data Treatment and Analysismentioning
confidence: 99%